#SochiProblems: Ignorance or Arrogance? - Laskin, Alexander V. (Instituto de Investigación en Relaciones Públicas, 2014)
The study focuses on the twitter conversations about the XXII Winter Olympics Games in Sochi, Russia. Specifically, the study collects and performs content analysis of the tweets tagged with the hashtag #SochiProblems. This study draws a random sample of tweets from every day of the games to achieve a 99% confidence level with 5% confidence interval and uses the framing theory to analyze this sample. The results allow us to determine what substantive and affective frames dominated in the twitter conversations tagged with #SochiProblems hashtag and what was the main focus of the tweets’ content.
#SochiProblems: ¿ignorancia o arrogancia?
Keywords: Relaciones públicas; Redes sociales; Public Relations; Communication; Olympics Games; Framing theory